Analysis of factors predicting the application of chemical pleurodesis for pneumothorax: An observational study. Issue 1 (7th January 2022) - Shimoda, Masafumi; Tanaka, Yoshiaki; Hiramatsu, Miyako; Morimoto, Kozo; Arakawa, Kenichi; Abe, Taro; Ito, Koki; Suga, Miyuri; Shiraishi, Yuji; Yoshimori, Kozo; Ohta, Ken
Abstract : Abstract: Chemical pleurodesis is performed in pneumothorax patients to treat nonresolving air leakage or prevent recurrence. However, factors that might predict the need for chemical pleurodesis remain unknown. Therefore, this study investigated predictive factors for the application of chemical pleurodesis for pneumothorax. We retrospectively analyzed 401 adult pneumothorax patients who underwent chest tube drain insertion during hospitalization at Fukujuji Hospital from January 2016 to December 2020. The patients were divided into 3 groups: the pleurodesis group, comprising 89 patients treated with chemical pleurodesis; the nonpleurodesis group, comprising 206 patients treated without chemical pleurodesis; and the surgical group, comprising 106 patients treated surgically. Data for patients in the pleurodesis group were compared to those in the nonpleurodesis or surgical group, and a predictive score of the application of chemical pleurodesis for pneumothorax was developed. Compared with the nonpleurodesis group, in the pleurodesis group, patient age was higher ( P  < .001), emphysema (n = 33 (37.1%) vs 70 (34.0%), P  = .045), and interstitial pneumonitis (n = 19 (21.3%) vs 19 (9.2%), P  = .022) were more common causes, and chest tube suction was more common (n = 78 (87.96%) vs n = 123 (59.7%), P  < .001). Similar results were found between the pleurodesis and surgical groups. We developed a score for predicting the application of chemical pleurodesis for pneumothorax, including the following factors: age ≥55 years; presence of emphysema and/or interstitial pneumonitis; and use of chest tube suction. The score for the pleurodesis group showed a high area under the receiver operating characteristic curve compared with that for the nonpleurodesis group (0.776 [95% confidence interval]: 0.725–0.827). With a score of 2 as the cutoff value, the sensitivity was 91.0% and the specificity was 52.4%. In a comparison between the pleurodesis and surgical groups, the predicting score showed the high AUC of 0.904 (95% confidence interval: 0.863–0.945). This study reveals predictive factors for the application of chemical pleurodesis and provides a predictive score including 3 factors.